Uji Aktivitas Mukolitik Perasan Daun Miana (Plectranthus scutellarioides (L.) R.Br.) Secara In Vitro: Mucolytic Activity Test of a Squeeze of Miana leaves (Plectranthus scutellarioides (L.) R.Br.) by in Vitro - Krismayani Krismayani; Fajar Prasetya; Febrina Mahmudah (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Mucolytics are drugs that can dilute airway secretions by preventing mucoprotein and mucopolysaccharide threads from being sputum. Empirically, the juice of miana leaves is used by the Toraja people to treat cough with pHlegm. There has been no testing of miana leaf juice as a mucolytic agent, therefore this study was conducted to see the mucolytic activity of miana leaf juice. The test was carried out in vitro using bovine intestinal mucus as a negative control and acetyl as a positive control. Mucolytic activity can be seen from the decrease in viscosity produced by each test sample. Samples were tested using a Rheosys viscometer with a temperature and pH that matched the pHysiological conditions of the body. The results showed that the concentration of 1% miana juice had a large mucolytic activity, compared to concentrations of 0.5%, 1.5, and 2%. The results of pHytochemical screening showed that miana leaf juice was positive for saponins and flavonoids which were thought to work in decreasing the viscosity of mucus.